Novel approaches to the treatment of sickle cell disease: the potential of histone deacetylase inhibitors. Issue 3 (June 2012) - Okam, Maureen M; Ebert, Benjamin L
Sickle cell disease (SCD) is a severe genetic disorder of hemoglobin causing vaso-occlusion. Patients suffer severe anemia, strokes, renal failure, pulmonary compromise and shortened life expectancy. Over 90, 000 people in the USA have SCD, and the options for therapy are limited and only partially effective. With the available therapies – hydroxyurea, blood transfusion, hydration and pain medicines – patients continue to suffer the long-term complications of the disease. This review focuses on the pathogenesis of SCD and the role of fetal hemoglobin in disrupting the polymerization of sickle hemoglobin. The authors review the compounds that induce fetal hemoglobin: hydroxyurea, which is currently US FDA approved, and the histone deacetylase inhibitors and discuss their role in the treatment of SCD and other β-hemoglobinopathies.